THE EFFECT OF INDIVIDUAL COUNSELING SERVICES ON REDUCING AGGRESSIVE BEHAVIOR AMONG ELEMENTARY SCHOOL STUDENTS - Chenda Dara; Ming Kiri; Nicholas Renaldo (Yayasan Adra Karima Hubbi, 2025)
Aggressive behavior among elementary school students is a pressing issue that disrupts the learning environment and affects students’ social-emotional development. Individual counseling services have been identified as an effective intervention to address such behaviors by targeting underlying emotional triggers and promoting self-regulation. This study aims to evaluate the effectiveness of individual counseling services in reducing aggressive behavior among elementary school students. A quasi-experimental research design with a pre-test and post-test control group format was employed. The study involved 60 elementary school students identified as exhibiting aggressive behaviors, divided into an experimental group receiving counseling services and a control group receiving standard classroom management. Data were collected through behavioral observation sheets, aggression scales, and interviews with teachers. The findings revealed a significant reduction in aggressive behaviors in the experimental group compared to the control group. Students in the experimental group demonstrated improved emotional regulation and conflict resolution skills, as observed in both school and social interactions. These results underscore the importance of individualized interventions in addressing aggressive behavior and fostering a positive school climate.